IMPLEMENTASI PENDIDIKAN MULTIKULTURAL SEBAGAI UPAYA PENGUATAN NILAI KARAKTER TOLERANSI SDN KAPUK MUARA 01 - Dian Fahrani (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the implementation of multicultural education as an effort to strengthen the value of the character of tolerance in students at SDN Kapuk Muara 01. The research method used is descriptive qualitative with a case study approach. In addition, the researcher intends to understand the social situation in depth. Data collection techniques researchers used several methods, namely interviews, documentation, and observation. The population of this study was SDN Kapuk Muara 01 grades 4 to 6, which amounted to 83 students. The results showed that the application of multicultural education at SDN Kapuk Muara 01 was included in the high category, based on the percentage value of the high category of 42%. While the students of SDN Kapuk Muara 01 have a moderate tolerance, based on the percentage value of the medium category of 35%.